Evaluation of Novel Multiplex Antibody Kit for Human Immunodeficiency Virus 1/2 and Hepatitis C Virus Using Sol-Gel Based Microarray. (17th September 2015) - Yun, Seung Gyu; Jang, Jin Woo; Lee, Jong Han; Lim, Chae Seung; Kim, Jinhong; Ki, Yeona; Jo, Minjoung; Kim, Soyoun
Abstract : Background . Microarrays enable high-throughput screening (HTS) of disease-related molecules, including important signaling proteins/peptides and small molecules that are in low abundance. In this study, we developed a multiplex blood bank screening platform, referred to as the Hi3-1 assay, for simultaneous detection of human immunodeficiency virus 1/2 (HIV 1/2) and hepatitis C virus (HCV). Methods . The Hi3-1 assay was tested using four panels (Panel 1, n = 4, 581 patient samples; Panel 2, n = 15 seroconversion samples; Panel 3, n = 4 performance samples; and Panel 4, n = 251 purchased positive control samples), and the results were collected by the Department of Laboratory Medicine, Korea University Medical College, Republic of Korea. The present study compares the sensitivity of the multiplex detection platform for both HIV and HCV using a sol-gel based microarray, which was based on a reference test (Architect HIV Ag/Ab Combo and Architect anti-HCV assays), in Korean patients. Results . The sensitivity of the multiplex detection platform for both HIV and HCV was 100%, and the specificity was 99.96% for HIV and 99.76% for HCV, which is equivalent to that of the reference test. Conclusion . We have successfully applied a novel screening technology to multiplex HIV and HCV diagnoses in a blood bank screening test.